Rotating detonation engine development and performance testing - Muhammad Yusri Nor @ Yahya, 1994-, author 611884; Mazlan Abdul Wahid 610961 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017